ETHICS AS ANTHROPOLOGY: CONSCIOUSNESS, AND PERSON SUBJECT TODAY. OF JACOB ANDRÉ (Disertaciones, 2017)
The ethical question falls today by its own weight. Many have believed that they could annul it, with the fear of returning to ancestral postulates. It matters, in truth, not to take lightly a crisis of the foundations that attacks the whole of human thought. However, the inevitability of the action does not condemn it therefore to arbitrariness. A severe vigilance with regard to abstractions should authorize a new beginning. The anthropological foundation of human behavior is proposed as a middle way between empiricist reductions-nihilistic intentions- and the desperate call to secular values: as if Moral was the minimum resource, but the last, for a time that can no longer with its problems.